INTEREST GROUP SESSION - QUALITATIVE RESEARCH: QUALITATIVE APPROACHES IN INVESTIGATING INTERGENERATIONAL FAMILY RELATIONSHIPS IN ADVANCED AGE. (11th November 2018) - Meystre, C; Koren, C; Stephens, C
Abstract: New family relationships have emerged with increase in life expectancy. Not only are relationships between family members likely to last longer, older individuals also more often repartner. This symposium presents three studies, each from a different country and continent, using a qualitative approach to learn more about the nature of intergenerational family relations and describe new challenges family members encounter. Koren and Lipman-Schiby focus on the relationship between Israeli adult grandchildren and their grandparents who repartnered. Interpretative phenomenological analysis shows various grandchildren experiences of relationship change with grandparent, influenced by the grandparent's partner. Jung and Jopp focus on the relationship between US adult children and their aging parents. Content analysis of the children's descriptions of this relationship show challenges, as well as benefits, and further shows that their relationship influences their general perception of aging. Meystre and colleagues (Switzerland) explore old parent-child relationships using an observational setting. Analysis is based on concrete discussions between parent and child and explores the links between language and relationship quality. The results of these studies underline that intergenerational family relationships in recently emerging family situations are characterized by different issues, for instance, concerning dependence/autonomy, and may lead to ambivalent feelings among family members. Qualitative approaches enable us to apprehend subjective experiences in context, and bring new insights in our understanding of family relationships through the life course. Discussant Dr. Stephens (New Zealand), expert on aging and health, will integrate concepts, draw conclusion and facilitate discussion on the complexity and importance of intergenerational family relations.